Cycle Time Reduction for Productivity Improvement in an Engine Assembly Industry - Chanathip Wongsomboon; Noppadol Maneerat; Jakkrit Thudthong; Sutikamon Sukasem; Amata Luangpol (My University, 2023)
The production process improvement is a solution to increase the efficiency of productivity. The improvement is applied to the production process gradually and continuously for the production process balancing. This research uses the cycle time and waste disposal, which are important tools that can be used to analyse the lost process time and waste in all aspects of business. There are guidelines for classifying the types of waste into seven groups. In addition, there are electric torque wrench to one workstation and production line balancing to reduce the cycle time. Finally, the production cycle time is reduced by 14 percents then the production cost is also reduced, and the company can get more profit.
Keywords: Management and Optimization Techniques; Quality and Supply Management; Manufacturing Process and Optimization